Social isolation during the COVID-19 pandemic can increase physical inactivity and the global burden of cardiovascular disease - Peçanha, Tiago; Goessler, Karla Fabiana; Roschel, Hamilton; Gualano, Bruno (American journal of physiology. Heart and circulatory physiology, 2020)
Emerging data indicate a substantial decrease in global physical activity levels during the period of social isolation adopted worldwide to contain the spread of the coronavirus disease 2019 (COVID-19). Confinement-induced decreases in physical activity levels and increases in sedentary behavior may provoke a rapid deterioration of cardiovascular health and premature deaths among populations with increased cardiovascular risk. Even short-term (1–4 wk) inactivity has been linked with detrimental effects in cardiovascular function and structure and increased cardiovascular risk factors. In this unprecedented and critical scenario, home-based physical activity programs arise as a clinically relevant intervention to promote health benefits to cardiac patients. Many studies have demonstrated the feasibility, safety, and efficacy of different models of home-based exercise programs in the primary and secondary prevention of cardiovascular diseases and major cardiovascular events among different populations. This body of knowledge can inform evidence-based policies to be urgently implemented to counteract the impact of increased physical inactivity and sedentary behavior during the COVID-19 outbreak, thereby alleviating the global burden of cardiovascular disease.